A Formação de professores no Brasil: um estudo das diretrizes curriculares nacionais para a formação inicial e continuada dos professores (2002-2015) - Bezerra, Adriana Mamede de Carvalho (2017)
This study is a production developed as a master's thesis, associated to the Post- Graduation Program in Education of the Federal University of Paraíba (UFPB), in the line of research in Educational Policies. It is an investigation about the policy of initial and continuing training of teachers of Basic Education in Brazil, guided by Resolutions CNE/CP 1/2002 and 2/2002, which establish the National Curricular Guidelines for the training of teachers of basic education; in addition to Resolutions CNE/CP 1/2006 and CNE / CP 2/2015 which deal respectively with the National Curricular Guidelines for the Graduation Course in Pedagogy and the definition of new guidelines for the initial and continuous training of teaching professionals of Basic Education. The methodology adopted was based on bibliographical and documentary research, with a qualitative approach. Our work was based on the studies of Freitas, H. (1999, 2002, 2003,2007a, 2007b), Sheibe (2001), Aguiar (2005), Brezezinski (1997, 2011), Freitas, L. (1992) and Dourado (2015). Our study discussed the teacher's initial and continued training and prioritized the National Common Base as a guiding principle of training. From the design of a new political project for teacher training, progress has been made in the legislation of the training policy of these professionals, and their profile has been re-dimensioned from the conception of teaching, which includes the articulated exercise in the teaching and learning processes and in the organization and management of Basic Education.